Pengembangan Media Interaktif Gambar Teknik Dasar Berbasis AI Menggunakan Genially dan Canva Untuk SMK Kelas X Teknik Pemesinan - M. Khalid Thirafi Taufikul Hakim; Marsono Marsono (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
Basic Engineering Drawing learning at SMKN 1 Tuban still faces challenges related to the limited use of interactive learning media, resulting in less optimal student understanding of conceptual materials. This study aimed to develop Artificial Intelligence (AI)-based interactive learning media using the Genially and Canva platforms and to determine its feasibility and practicality. The study employed a Research and Development (R&D) method using the ADDIE model up to the implementation stage. The subjects were tenth-grade students of the Machining Engineering program at SMKN 1 Tuban in a small-group trial. Data were collected through observation, interviews, questionnaires, and validation sheets, then analyzed descriptively using percentage techniques. The results showed that the developed media achieved a material expert validation score of 89% and a media expert validation score of 92%, both categorized as very feasible. In addition, the practicality test based on student responses obtained a percentage of 86.2%, categorized as very practical. The media integrates visual materials, animations, interactive navigation, quizzes, and AI-based automatic feedback to support a more engaging learning experience. Therefore, the developed AI-based interactive learning media is considered feasible and practical for use in Basic Engineering Drawing learning at vocational high schools.